Double Standards in International Relations: How Realpolitik Considerations Deter Muslim-Majority States from Defending Muslims in China - Brasnett, Jonathan (Université d'Ottawa / University of Ottawa, 2021)
In recent years, China has become an increasingly influential actor in Muslim-majority countries the world over. This is despite growing international condemnation of Beijing’s imprisonment of Muslims living in northwestern Xinjiang province, in so-called "vocational training schools" where their religious identities are forcibly assimilated under the guise of counter-extremism. Nevertheless, Muslim-majority countries have remained silent or even supportive of China's treatment of its Muslim minorities. This seemingly contradictory policy position is frequently explained by citing these countries’ dependence on Chinese trade and investment in their economic and infrastructural development, however this argument inadequately assesses other important factors behind these countries’ support for China’s treatment of its Muslim minorities. Beyond the theory of economic necessity and the equally realist consideration of security ties, this research further posits that Muslim-majority states support or defend China’s treatment of Muslims in order to secure Chinese ideological support to defend themselves from reproach against their own domestic policies towards separatist movements and religious extremists. To evaluate these hypotheses, this thesis examines the engagement of some key Muslim-majority states with China by analyzing realpolitik factors like (1) economic relations; and (2) security and military cooperation; as well as more ideological factors, namely whether or not they share a common vulnerability to (3) domestic secessionist movements challenging their authority; or to (4) religious extremism that threatens state security. This research examines the economic and security relations between China and six of the most geopolitically significant Muslim- majority countries (Egypt, Saudi Arabia, Iran, Indonesia, Pakistan and Turkey), as well the influence of secessionism and religious extremism in each country. It then assesses the analytical validity of these four hypotheses, and concludes that the ideological considerations consisting of common vulnerability to secessionism and/or religious extremism, exhibited the greatest explanatory power for predicting Muslim-majority countries’ level of support for China's treatment of Muslims. Although realpolitik considerations like economic and security cooperation with China can also clearly be seen to influence the position of Muslim-majority countries on this issue, ideological factors like obtaining Chinese support for their suppression of secessionist movements or religious extremism are clearly paramount. In addition to these four variables, this research also briefly acknowledges the explanatory potential of other ideological factors in influencing the support of Muslim-majority countries for China's policies towards its Muslim minorities. These include factors like regime type, the prevalence of anti- American sentiment, as well as the desire to form an alliance with China against Western democracies and the norms and standards they espouse in multilateral organizations. Ultimately, this dissertation demonstrates that China has already achieved widespread political and ideological support among the developing countries of the Global South, including many Muslim-majority countries. If Western democracies wish to exert pressure on China to change its behaviour, they will first need to win back the support of the Global South by offering a suitable alternative source of political, economic and security support, while foregoing neocolonial demands to enact changes to their domestic political systems.
Keywords: China; Islam; Governance; Diplomacy; Soft Power; Middle East; North Africa; Muslim; Egypt; Saudi Arabia; Iran; Pakistan; Indonesia; Turkey; Uyghur